Effects of 16 Weeks of Methylphenidate Treatment on Actigraph-Assessed Sleep Measures in Medication-Naive Children With ADHD - Solleveld, Michelle M.; Schrantee, Anouk; Baek, Hee Kyung; Bottelier, Marco A.; Tamminga, Hyke G. H.; Bouziane, Cheima; Stoffelsen, Reino; Lucassen, Paul J.; Van Someren, Eus J. W.; Rijsman, Roselyne M.; Reneman, Liesbeth (Frontiers in Psychiatry, 2020)
Methylphenidate (MPH) improves behavioral symptoms of Attention-Deficit/Hyperactivity Disorder (ADHD). Its effects on sleep, however, are insufficiently known, as trials with MPH in medication-naïve children were so far restricted to relatively short trial durations. Here, we assessed effects of prolonged MPH treatment on sleep in medication-naive boys in a 16-weeks double-blind, placebo controlled, multicenter clinical trial with immediate-release MPH (ePOD-MPH trial, NTR3103). Seventy-five medication-naive boys, aged 10-12 years, were screened for eligibility using ADHD DSM-IV criteria. Sleep was assessed using actigraphy, diaries and questionnaires prior to randomization, in week 8, and 1 week after trial end. Fifty boys (mean age 11.4y, SD 0.9) were randomized to MPH or placebo. Linear mixed model analysis demonstrated a significant time-by-treatment interaction effect (p=0.007) on sleep efficiency. Post-hoc analyses demonstrated that the two groups did not differ from each other (p=0.94) during treatment (week 8), but that sleep efficiency was significantly improved in the MPH (p=0.005), but not placebo group (p=0.87) 1 week after trial end. The lack of MPH’s negative effects on sleep during treatment differ from most previous studies and could be explained by the relatively long trial duration in our study and the medication-naïve status of our sample; suggesting that evaluating sleep problems only shortly after treatment onset presents an incomplete picture, because it might not be representative for sleep quality after longer treatment periods. Our findings of improved sleep after trial end could be due to rebound effects or longer-term effects of MPH treatment and therefore require replication.